Information as superheroes / Nadia Nur Amalina Zulkanain and Norhidayah Abdul Aziz - Zulkanain, Nadia Nur Amalina; Abdul Aziz, Norhidayah (Faculty of Information Management, 2015)
Information helps to determine its overall usefulness. There are three forms of information. They are written form, aural form and visual form. Information can be transferred through several mediums. Information can be considered as superhero that helps people in decision making, completing tasks and differentiate probability. Superhero is a fictional character that has amazing powers and ability to help people. There are several information characteristics that are compatible with certain superheroes. They are Superman, Spiderman, Dash, Elastigirl and Naruto. Superhero influences our life similar with information; it plays a major role in the life of humans and gives a strong effect.